Arrangement of Ceramides in the Skin: Sphingosine Chains Localize at a Single Position in Stratum Corneum Lipid Matrix Models - Beddoes, Charlotte M. (Langmuir, 2020)
[Image: see text] Understanding the structure of the stratum corneum (SC) is essential to understand the skin barrier process. The long periodicity phase (LPP) is a unique trilayer lamellar structure located in the SC. Adjustments in the composition of the lipid matrix, as in many skin abnormalities, can have severe effects on the lipid organization and barrier function. Although the location of individual lipid subclasses has been identified, the lipid conformation at these locations remains uncertain. Contrast variation experiments via small-angle neutron diffraction were used to investigate the conformation of ceramide (CER) N-(tetracosanoyl)-sphingosine (NS) within both simplistic and porcine mimicking LPP models. To identify the lipid conformation of the twin chain CER NS, the chains were individually deuterated, and their scattering length profiles were calculated to identify their locations in the LPP unit cell. In the repeating trilayer unit of the LPP, the acyl chain of CER NS was located in the central and outer layers, while the sphingosine chain was located exclusively in the middle of the outer layers. Thus, for the CER NS with the acyl chain in the central layer, this demonstrates an extended conformation. Electron density distribution profiles identified that the lipid structure remains consistent regardless of the lipid’s lateral packing phase, this may be partially due to the anchoring of the extended CER NS. The presented results provide a more detailed insight on the internal arrangement of the LPP lipids and how they are expected to be arranged in healthy skin.